Pengembangan Pengukuran Hasil Tes Kebugran Jasmani Cabang Olahraga Tonnis Pada Murid Pase C SDN 1 Kayuagung Berbasis Aplikasi - Wibowo, Galih Mardi; Hartati, Hartati; Iyakrus, Iyakrus; Usra, Meirizal; Yusfi, Herri; Ramadhan, Arizky (Universitas Hamzanwadi, 2024)
The purpose of this research is to create and build a technology application that assesses the results of a special physical fitness test for tonnis. This research uses the ADDIE development method which starts at the analysis, design, development, implementation, and evaluation stages. The subjects of this study were students of SDN 1 Kayuagung grade 6 at the age of 11-12 years, totaling 30 students. This research was validated by 3 experts, the first material expert to validate the instrument and norms whether it is in accordance with the results of 88%, the second media expert to validate the calculation whether it is appropriate by 85% and the third linguist to validate whether it is in accordance with standard spelling by 92% using a questionnaire of various questions. Of the three validations there is an average of 88%, the application of measuring the results of the physical fitness test of storing and managing test results is feasible to use. However, from the statistical test results of the trial with a normality test of 0.200 > 0.05 homogeneity test of Sig. 0.793 > 0.05 and independent sample t test of 0.379 > 0.05. From the results of the study it can be concluded that it is valid, practical, and effective. and can be used as a storage medium, managing student fitness test results both at school and in extracurricular school forms.